A Feasible Approach to Design a Cmos Domino Circuit at Low Power VLSI Application Design (International Journal of Engineering and Computer Science, 2015)
Dynamic logic style is used in high performance circuit design because of its fast speed and less transistors requirement as compared to CMOS logic style. But it is not widely accepted for all types of circuit implementations due to its less noise tolerance and charge sharing problems. A small noise at the input of the dynamic logic can change the desired output. Domino logic uses one static CMOS inverter at the output of dynamic node which is more noise immune and consuming very less power as compared to other proposed circuit. In this paper we have proposed a novel circuit for domino logic which has less area and has less power-delay product (PDP) as compared to previous reported articles. Low PDP is achieved by using semi-dynamic logic buffer and also reducing leakage current when PDN is not conducting. Then comparison analysis has been carried out by simulating the circuits in 90nm CMOS process technology from TSMC using Tanner EDA 14.11..